Preliminary Testing of Hybrid Catalytic-Plasma Reactor for Biodiesel Production Using Modified-Carbon Catalyst - Luqman Buchori; Istadi Istadi; Purwanto Purwanto; Anggun Kurniawan; Teuku Irfan Maulana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Preliminary testing of hybrid catalytic-plasma reactor for biodiesel production through transesterification of soybean oil with methanol over modified-carbon catalyst was investigated. This research focused on synergetic roles of non-thermal plasma and catalysis in the transesterification process. The amount of modified-carbon catalyst with grain size of 1.75 mm was placed into fixed tubular reactor within discharge zone. The discharge zone of the hybrid catalytic-plasma reactor was defined in the volume area between high voltage and ground electrodes. Weight Hourly Space Velocity (WHSV) of 1.85 h-1 of reactant feed was studied at reaction temperature of 65 oC and at ambient pressure. The modified-carbon catalyst was prepared by impregnation of active carbon within H2SO4 solution followed by drying at 100 oC for overnight and calcining at 300 oC for 3 h. It was found that biodiesel yield obtained using the hybrid catalytic-plasma reactor was 92.39% and 73.91% when using active carbon and modified-carbon catalysts, respectively better than without plasma. Therefore, there were synergetic effects of non-thermal plasma and catalysis roles for driving the transesterification process.